Transdisciplinary in Architecture as a digital change: back to the future - Correia, R. (2018)
This paper outlines a historic perspective of transdisciplinary in digital architecture through the work of several key figures (architects, computer scientists, mathematics, engineers and artists) from the 20th century. Transdisciplinary Digital Architecture deals with digital means and science. The research methodology adopted in this study allows analyzing historic documentation available on internet (text, audio, picture, video) to establish the links between them and their relevance to present time digital architecture. This paper aims to describe the first preliminary results of the research to establish a new theory of the digital in architecture based on a body of theoretical foundations that link “first age” transdisciplinarity to Bauhaus teaching methods, and to early use of computers in architecture.